COMPARATIVE ANALYSIS OF TRANSPORTATION SYSTEM IN AMERICA, ENGLAND, AND INDONESIA - Haryono Haryono (Institut Transportasi dan Logistik Trisakti, 2015)
A growing society needs a good transportation system that supports the ongoing activities of large business community. Road transport system is a universal and integral system without boundaries. Existence of people does depend on transportation. Different countries implement various transportation systems with different traits and characteristics. The study was conducted by looking at the network of transportation system. The researchers are comparing the transportation system in United States, United Kingdom and Indonesia. The fundamental difference is the orientation of the government. In terms of the provision of public transport services, the Indonesian government is still in the primary stage oriented to provide public transportation for people to arrive at the destination, while other countries have been at the secondary stage of comfort-oriented and safety-concern. They have even been to the tertiary stage that is the luxury-attention.